2018
DOI: 10.2217/nnm-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Nanomedicine: Mechanisms, Obstacles and Strategies

Abstract: Targeting nanoparticles to cancers for improved therapeutic efficacy and decreased side effects remains a popular concept in the past decades. Although the enhanced permeability and retention effect serves as a key rationale for all the currently commercialized nanoformulations, it does not enable uniform delivery of nanoparticles to all tumorous regions in all patients with sufficient quantities. Also, the increase in overall survival is often modest. Many factors may influence the delivering process of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 156 publications
0
22
0
Order By: Relevance
“…[ 2 ] However, due to the intrinsic limitations associated with those clinical modalities, the therapeutic efficacy very often exhibits decreased performance. [ 3 ] For example, patients receiving chemotherapy are subject to its accompanied side effects. This is because most of the anticancer drugs used in chemotherapy are poor water‐soluble, highly toxic, lack of targeting property, and developing multidrug resistance (MDR).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] However, due to the intrinsic limitations associated with those clinical modalities, the therapeutic efficacy very often exhibits decreased performance. [ 3 ] For example, patients receiving chemotherapy are subject to its accompanied side effects. This is because most of the anticancer drugs used in chemotherapy are poor water‐soluble, highly toxic, lack of targeting property, and developing multidrug resistance (MDR).…”
Section: Introductionmentioning
confidence: 99%
“…can accumulate in tumors by passive retention mechanism (so-called enhanced permeability and retention effect, EPR), due to the irregular epithelium, decreased interstitial fluid uptake, and weakened lymphatic drainage of tumor vasculature (Bertrand et al, 2014;H. Li, Jin, Wan, Wu, & Wei, 2018).…”
Section: Nanocarrier Descriptionmentioning
confidence: 99%
“…In case of drug delivery applications, nanoparticles have been shown to protect the drugs from degradation, improve their solubility, prolong blood half‐life and modulate pharmacokinetic properties, as well as to provide the targeted delivery and controlled drug release (Bertrand, Wu, Xu, Kamaly, & Farokhzad, ). What is more, it has been found that nanoparticles can accumulate in tumors by passive retention mechanism (so‐called enhanced permeability and retention effect, EPR), due to the irregular epithelium, decreased interstitial fluid uptake, and weakened lymphatic drainage of tumor vasculature (Bertrand et al, ; H. Li, Jin, Wan, Wu, & Wei, ). The possibility of conjugation of nanoparticles with targeting moieties such as peptides, antibodies, carbohydrates, or folic acid can further enhance specific transport of the drugs to their sites of action (Friedman, Claypool, & Liu, ).…”
Section: Nanotechnology For Enhanced Efficiency Of Pdtmentioning
confidence: 99%
“…These theranostic SPION-DOX PNP thus reflect the real-time characteristics of the tumor in each patient and could allow for earlier disease detection, more accurate prognostic information and an enhanced ability to monitor the efficacy of treatment [15]. Besides, the evaluation of the NP accumulation in healthy tissues would allow us to assess the risk of patients developing off-target side effects or to screen patients who are likely to respond positively to the treatment [16].…”
Section: Introductionmentioning
confidence: 99%